Cancer Phototherapy: Multimodal‐Imaging‐Guided Cancer Phototherapy by Versatile Biomimetic Theranostics with UV and γ‐Irradiation Protection (Adv. Mater. 17/2016). Issue 17 (May 2016) - Lin, Jing; Wang, Min; Hu, Hao; Yang, Xiangyu; Wen, Bronte; Wang, Zhantong; Jacobson, Orit; Song, Jibin; Zhang, Guofeng; Niu, Gang; Huang, Peng; Chen, Xiaoyuan
Abstract : On page 3273, P. Huang, X. Chen, and co‐workers report a versatile biomimetic theranostic agent based on magnetic melanin nanoparticles (MMNs). This agent enables guided photothermal cancer therapy combining positron‐emission tomography (PET), magnetic resonance (MR), photoacoustic (PA), and photothermal (PT) for multimodal‐imaging. MMNs also exhibit efficient shielding against UV‐ and γ‐irradiation.